2018
DOI: 10.1007/s00234-018-2080-7
|View full text |Cite
|
Sign up to set email alerts
|

Incidental findings on cervical spine computed tomography scans: overlooked and unimportant?

Abstract: Cervical incidentalomas vary in rates from ARSA (0.86%) to LC (9.4%). They are rarely mentioned in radiologists' reports. Whether improved vigilance and reporting of these incidentalomas would benefit patient care should be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The field of view in the oral and maxillofacial region often includes a region from the base of the brain to the apex of the lung, and thus oral radiologists need to take care to observe adjacent regions in the images. Indeed, many incidental findings have been described in previous reports (6)(7)(8)(9)(19)(20)(21). The thyroid gland should be focused upon because its entirety is frequently included in CT images of the oral and maxillofacial region.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The field of view in the oral and maxillofacial region often includes a region from the base of the brain to the apex of the lung, and thus oral radiologists need to take care to observe adjacent regions in the images. Indeed, many incidental findings have been described in previous reports (6)(7)(8)(9)(19)(20)(21). The thyroid gland should be focused upon because its entirety is frequently included in CT images of the oral and maxillofacial region.…”
Section: Discussionmentioning
confidence: 97%
“…With the development of imaging modalities in recent years, there has been an increase in the identification of incidental lesions on images obtained by CT and MRI, as advanced imaging modalities (6)(7)(8)(9)(19)(20)(21). In particular, CT machines are maintained at many facilities, and it is possible to obtain more detailed diagnoses by CT immediately after lesions are suspected on plain radiographs of the oral and maxillofacial region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found discrepancies between re-interpretation and original radiology reports, in which both under- and overreads exist. Beheshtian et al [ 13 ] found that only 20 out of 701 incidentalomas (2.9%) were documented in 2116 original cervical spine CT reports. In contrast, Barboza et al [ 4 ] identified a 9.1% missed rate in 1256 official trauma cervical spine CT reports, in which the majority (75%) of incidentalomas were nontraumatic findings.…”
Section: Discussionmentioning
confidence: 99%
“…This examination typically covers the skull base to T1 or T2 vertebrae, and is therefore inclusive of many structures within the thoracic inlet, such as bones, pleurae and lung apices [ 1 , 10 , 11 ]. A few previous investigations have reported a high prevalence of incidental CT findings on trauma cervical spine CT [ 4 , 12 , 13 ]. Based on our experience, a careful review of thoracic inlet images included in a cervical spine CT of trauma patients can reveal potentially important findings not shown on a concurrent pCXR.…”
Section: Introductionmentioning
confidence: 99%